2015
DOI: 10.1088/0953-8984/27/46/465301
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-dependent spin-charge transport and thermopower through a ZSiNR-based FM/normal/FM junction

Abstract: We investigate the spin-dependent transport and spin thermopower for a zigzag silicene nanoribbon (ZSiNR) with two ends covered by ferromagnets (FMs) under the modulation of a perpendicular electric field, where we take the 6- and 7-ZSiNR to exemplify the effect of the even- and odd-N ZSiNRs, respectively. By using the nonequilibrium Green's function approach, it is demonstrated that a ZSiNR-based FM/normal/FM junction still shows an interesting symmetry-dependent property although the σ mirror plane is absent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
0
19
2
Order By: Relevance
“…The results shall display that there is an entire difference in the transport properties between perfect and imperfect ZGNRs. As we known all perfect ZGNRs have similar metallic band structures [17,18] and at a two-terminal system, they exhibit distinctly different transport behaviors under bias voltage, depending on whether their geometries are symmetrical or not [19,20]. However, the transport gaps can be observed for all present systems under zero temperature and zero bias, which is far from the cases above.…”
Section: Introductionmentioning
confidence: 67%
“…The results shall display that there is an entire difference in the transport properties between perfect and imperfect ZGNRs. As we known all perfect ZGNRs have similar metallic band structures [17,18] and at a two-terminal system, they exhibit distinctly different transport behaviors under bias voltage, depending on whether their geometries are symmetrical or not [19,20]. However, the transport gaps can be observed for all present systems under zero temperature and zero bias, which is far from the cases above.…”
Section: Introductionmentioning
confidence: 67%
“…Some previously published works reported that zigzag silicene nanoribbons with even and odd widths have very different current-voltage relationships, magnetoresistance and thermopower behavior, and these differences were attributed to the different parities of their 𝜋 and 𝜋 ⋆ bands. [31,32] However, our results further point out that the even-𝑀 and odd-𝑀 positions of central nanoribbons with the same width also have very different transport properties. This difference can be explained by noting that the even-𝑀 and odd-𝑀 cases result in two distinct types of interfaces between the wide and narrow segments with different atomic configurations.…”
mentioning
confidence: 63%
“…In the case of graphene, silicene, and silographene, almost complete calculations for spin transport have been performed. 49,[61][62][63][64][65] In addition to the investigation of conductance in P and AP configurations as well as arbitrary relative angles of magnetization of the leads, calculations of MR and STT in the spin valve device with CPP structure have also been performed, and the results have been presented.…”
Section: Introductionmentioning
confidence: 99%